Similar pharmacokinetics and pharmacodynamics of a new biosimilar and reference insulin aspart in healthy Chinese males - Liu, Hui; Yu, Hongling; Sun, Lisi; Qiao, Jingtao; Wan, Sainan; Li, Shuang; Li, Jiaqi; Tan, Huiwen; Yu, Yerong (Scientific reports, 2021)
Insulin aspart (IAsp) is one of the main therapies used to control blood glucose after a meal. This study aimed to compare the pharmacokinetics (PK) and pharmacodynamics (PD) of 2 rapid-acting IAsp products: a new IAsp biosimilar (RD10046) and NovoRapid. In a single-center, randomized, single-dose, 2-period, crossover, euglycemic clamp study (registry number: CTR20180517, registration date: 2018-05-30), healthy Chinese males were randomized to receive 0.2 U/kg of the IAsp biosimilar RD10046 and NovoRapid under fasted conditions on two separate occasions. PK and PD were assessed for up to 10 h. Of the 30 randomized subjects, all 30 completed both treatment periods. The PK (area under the curve [AUC] of total IAsp; maximum observed IAsp concentration [C max ]) and PD (maximum glucose infusion rate [GIR max ]; total glucose infusion during the clamp [AUC GIR,0–10h ]) were similar between the new IAsp biosimilar RD10046 and NovoRapid. In all cases, the 90% CIs for the ratios of the geometric means were completely contained in the prespecified acceptance limits of 0.80–1.25. No hypoglycemic events, allergic reactions, or local injection adverse reactions occurred in this trial. We concluded that the studied IAsp biosimilar (RD10046) was bioequivalent to NovoRapid.